2016
DOI: 10.1364/oe.24.010313
|View full text |Cite
|
Sign up to set email alerts
|

Empirical formulas for calculating loss in hollow core tube lattice fibers

Abstract: In this paper scaling laws governing loss in hollow core tube lattice fibers are numerically investigated and discussed. Moreover, by starting from the analysis of the obtained numerical results, empirical formulas for the estimation of the minimum values of confinement loss, absorption loss, and surface scattering loss inside the transmission band are obtained. The proposed formulas show a good accuracy for fibers designed for applications ranging from THz to ultra violet band.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 23 publications
4
35
0
1
Order By: Relevance
“…IC-kagome and IC-tubular fibers can therefore exhibit very close dispersion profiles despite their apparent geometrical differ-ence, as long as they have the same radius and silica strut thickness. However, as losses strongly depend on the cladding geometry [29], this simple tube-type model is not suited to infer fiber losses.…”
Section: Dispersion and Group Velocity Matching Conditions In Hollow-mentioning
confidence: 99%
“…IC-kagome and IC-tubular fibers can therefore exhibit very close dispersion profiles despite their apparent geometrical differ-ence, as long as they have the same radius and silica strut thickness. However, as losses strongly depend on the cladding geometry [29], this simple tube-type model is not suited to infer fiber losses.…”
Section: Dispersion and Group Velocity Matching Conditions In Hollow-mentioning
confidence: 99%
“…The latest experimental work on a tube-lattice fiber showed that a propagation loss of approximately 5 dB/m in the fundamental transmission window around 0.27 THz had been achieved, and losses of 1 dB/m in higher order transmission windows were T inferred, being too low to measure reliably [22]. However, as a type of anti-resonant fiber, the tube-lattice fiber in [22] supports a high number of modes, especially in higher order transmission windows due to the relatively large core size, resulting in mode-competition problems [ 32 ], [ 33 ]. Triangular-lattice microstructured fibers fabricated by stacking were shown to guide terahertz waves [23], [24], and a propagation loss less than 0.87 dB/m around 0.77 THz was achieved [23].…”
mentioning
confidence: 99%
“…2(b) for its definition] whose values range from 0 for a circular core contour with no negative curvature cups, to b 1 for a contour having circular cups, to b > 1 elliptical cups. In addition to the aforementioned geometry effect, thinner silica cladding strut t is also desired to reduce the optical overlap and CL and to increase the bandwidth of the fiber transmission windows [7,18]. Indeed, the IC fibers exhibit several transmission windows having cutoffs associated with core mode coupling with the cladding glass modes at wavelengths λ l 2t∕l − 1 ffiffiffiffiffiffiffiffiffiffiffi ffi n 2 − 1 p , with n being the silica glass index and l a positive integer representing the radial-number index of the cladding mode.…”
mentioning
confidence: 99%
“…Here, the HC-PCF strut thickness is fixed to t 600 nm, and the results show a decrease in CL by ∼2 orders of magnitude when the b is increased from 0.25 to 1.25. Following the approach reported in [18], we fitted the CL data to empirically extract a scaling law of the CL with t, b, and λ. [2,18].…”
mentioning
confidence: 99%
See 1 more Smart Citation